2013
DOI: 10.1039/c3cc45597a
|View full text |Cite
|
Sign up to set email alerts
|

π-Conjugated polyHIPEs as highly efficient and reusable heterogeneous photosensitizers

Abstract: π-Conjugated microporous polyHIPEs are synthesized via Suzuki cross-coupling. The polymeric backbone consists of electron donor and acceptor moieties with suitable energetic characteristics to promote the efficient photosensitizing ability for the activation of singlet oxygen, showing extraordinarily high stability. The reaction can be carried out in a continuous flow reaction set-up, realizing complete conversion of α-terpinene into ascaridole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 23 publications
1
72
0
Order By: Relevance
“…[18] As an alternative to the traditional oxidebased semiconductor photocatalysts, CMPs have emerged as an ew class of robusta nd efficient heterogeneneous visiblelight photocatalysts owing to their semiconductor-range bandgaps and excellenta bsorption of visible light. [19] Previous studies by variousg roups demonstrate that CMPs can serve as effective visible-light photocatalysts forn ot only photoredox reactions, such as molecular oxygen activation, [20] selectiveo xidation of organic sulfides, [21] CÀCb ond formation, [22] reductive dehalogenation, [23] and oxidative hydroxylation of arylboronic acids, [24] buta lso free-radical and cationic polymerization and [25] hydrogen evolution. [26] It was reported that the redox potentials of homogeneous transition-metal-based organometallicc omplexes can be adjusted by modifyingt he metal center and/ors urrounding ligands to meet the activation energy of specific organic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[18] As an alternative to the traditional oxidebased semiconductor photocatalysts, CMPs have emerged as an ew class of robusta nd efficient heterogeneneous visiblelight photocatalysts owing to their semiconductor-range bandgaps and excellenta bsorption of visible light. [19] Previous studies by variousg roups demonstrate that CMPs can serve as effective visible-light photocatalysts forn ot only photoredox reactions, such as molecular oxygen activation, [20] selectiveo xidation of organic sulfides, [21] CÀCb ond formation, [22] reductive dehalogenation, [23] and oxidative hydroxylation of arylboronic acids, [24] buta lso free-radical and cationic polymerization and [25] hydrogen evolution. [26] It was reported that the redox potentials of homogeneous transition-metal-based organometallicc omplexes can be adjusted by modifyingt he metal center and/ors urrounding ligands to meet the activation energy of specific organic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic strategies have been explored to help forge the product format during synthesis of these CMPs. These include electropolymerization (thin films), 8 emulsion polymerization (monoliths), 9 aerogels 10 and even soluble materials. 11 However, these strategies are still under-explored with large scope for further developments.…”
mentioning
confidence: 99%
“…CMP-20b, CMP-22,C MP-23, and CMP-24 have been found to be efficient photosensitizerst hat can generates inglet oxygen ( 1 O 2 )u nder irradiation. [41][42][43][44] CMP-20bb ased on benzothiadiazole as ab uilding block was developed by Vilela et al by palladium-catalyzedS onogashira coupling polycondensation. [41] By addition of SiO 2 NPs during preparation of CMP-20b, surface areas can be easily tuned.…”
Section: Cmps For Heterogeneous Photocatalytic Applicationsmentioning
confidence: 99%